Revision of Post-Endoscopic Discectomy: A Review - ALSHARAF, Yusuf; Alsaif, Mohamed; Sayed, Yakub (International Journal of Innovative Research in Medical Science, 2023)
This review focuses on the recurrence of lumbar disc herniation after percutaneous endoscopic discectomy (PED) and the revision surgery options available for patients who require further treatment. PED is a minimally invasive surgical technique used to treat herniated discs in the lumbar spine. Although PED has many advantages over traditional open decompression and fusion surgery, recurrent herniation is a common complication that can lead to the need for revision surgery. It will provide insights into strategies for minimizing complications and improving outcomes of post-endoscopic revision discectomy. The goal is to assist clinicians in selecting the most appropriate revision surgery option for their patients based on individual risk factors and other relevant factors. Ultimately, the review aimed to improve patient outcomes and reduce the need for repeat surgery in cases of recurrent herniation following PED. Various surgical techniques have been described for revision procedures, including repeated endoscopic discectomy, open discectomy, minimally invasive microdiscectomy, and fusion. The choice of technique depends on the specific indications and individual patient characteristics. The review will discuss common options for revision surgery, including minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF), micro-endoscopic discectomy (MED), and PED. Factors that increase the risk of recurrence after primary PED surgery, such as advanced age, obesity, and Modic changes, will also be discussed. Further research and long-term follow-up studies are warranted to enhance our understanding of the optimal management strategies and outcomes of post-endoscopic discectomy revision.